2014
DOI: 10.3109/10641963.2014.881843
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular function alterations induced by acute paradoxical sleep deprivation in rats

Abstract: Sleep loss has been implicated in triggering the hypertension. The goal of the present study was investigated the possible mechanisms underlying cardiovascular alterations after acute paradoxical sleep deprivation (PSD). Male Wistar rats were assigned in two experimental groups: (1) control and (2) PSD for 24 h using the modified single platform method. Paradoxical sleep deprived rats exhibited higher blood pressure, heart rate (HR) and impaired baroreceptor sensitivity. After pharmacological autonomic double … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…The other study demonstrated that OSAS is the most common secondary etiology in patients with resistant hypertension [22]. Consistent with the present study, previous experimental studies also reported that acute REM sleep deprivation is associated with arterial hypertension [23,24]. Increase of sympathetic nervous system (SNS) activity, increase of vascular resistance, activation of the renin-angiotensin-aldosterone system, and increase of arterial stiffness following sleep loss and hypoxemia are some involving factors in this type of hypertension [25][26][27].…”
Section: Discussionsupporting
confidence: 88%
“…The other study demonstrated that OSAS is the most common secondary etiology in patients with resistant hypertension [22]. Consistent with the present study, previous experimental studies also reported that acute REM sleep deprivation is associated with arterial hypertension [23,24]. Increase of sympathetic nervous system (SNS) activity, increase of vascular resistance, activation of the renin-angiotensin-aldosterone system, and increase of arterial stiffness following sleep loss and hypoxemia are some involving factors in this type of hypertension [25][26][27].…”
Section: Discussionsupporting
confidence: 88%
“…According to Kato et al, after one night of sleep deprivation the arterial blood pressure increases and muscle sympathetic nerve activity decreases [24]. Other studies realized by Almeida FR et al suggest that acute paradoxical sleep loss (REM sleep) induces autonomic imbalance expressed by impaired baroreflex sensitivity, cardiovascular disfunctions, increased arrhythmia susceptibility and also changes related to oxidative stress or other cerebral pathologies [25][26][27]. The variation of arterial blood pressure in our study can be associated with the alteration of baroreflex sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…Pre-ischemic and reperfusion HR were higher in the SD group than in controls, which is consistent with the reports by others. Sgoifo et al, 19 Carvalho et al, 20 and Almeida et al 21 have reported that SD rats exhibited an increased HR and were vulnerable to ventricular arrhythmias. The mechanism of action of SD on HR during perfusion and reperfusion is not completely understood.…”
Section: Discussionmentioning
confidence: 99%